INVESTMENT FOR SUSTAINABLE DEVELOPMENT OF THE AGRARIAN SECTOR (International Journal of Innovative Technologies in Economy, 2018)
Theoretical, methodological and practical aspects of the investment trends in the agrarian business to ensure sustainable development of the agrarian sphere have been studied. Essence of the concept "investment appeal" has been justified and the environmental impact on investment appeal of enterprise has been defined. The relationship between investment appeal and investment potential as economic categories, features of investment attraction in the agrarian business as well as investment mechanisms to ensure sustainable development of the agrarian sector have been analyzed.